Environmental control of plant nuclear gene expression by chloroplast redox signals - Pfalz, Jeannette; Liebers, Monique; Hirth, Matthias; Gruebler, Bjoern; Holtzegel, Ute; Schroeter, Yvonne; Dietzel, Lars; Pfannschmidt, Thomas (Frontiers in Plant Science, 2012)
Plant photosynthesis takes place in specialised cell organelles, the chloroplasts, which perform all essential steps of this process. The proteins involved in photosynthesis are encoded by genes located on the plastid and nuclear genomes. Proper function and regulation of light harvesting and energy fixation thus requires a tight coordination of the gene expression machineries in the two genetic compartments. This is achieved by a bi-directional exchange of information between nucleus and plastids. Signals emerging from plastids report the functional and developmental state of the organelle to the nucleus and initiate distinct nuclear gene expression profiles, which trigger responses that support or improve plastid functions. Recent research indicated that this signalling is absolutely essential for plant growth and development. Reduction/oxidation (redox) signals from photosynthesis are key players in this information network since they do report functional disturbances in photosynthesis, the primary energy source of plants. Such disturbances are caused by environmental fluctuations for instance in illumination, temperature or water availability. These environmental changes affect the linear electron flow of photosynthesis and result in changes of the redox state of the components involved (e.g. the plastoquinone pool) or coupled to it (e.g. the thioredoxin pool). Thus, the changes in redox state directly reflect the environmental impact and serve as immediate plastidial signals to the nucleus. The triggered responses range from counterbalancing reactions within the physiological range up to severe stress responses including cell death. This review focuses on physiological redox signals from photosynthetic electron transport, their relation to the environment, potential transduction pathways to the nucleus and their impact on nuclear gene expression.